Terms extractions: an approach for requirements reuse - Bakar, Noor Hasrina; Mohd Kasirun, Zarinah; Salleh, Norsaremah (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper presents a solution to a requirements reuse problem that utilises natural language processing and information retrieval technique. We proposed a semi-automated approach to extract the software features from online software review to assist the process to reuse natural language requirements. We have conducted an experiment to compare the manual feature extraction versus the semi-automated feature extraction. We used compilations of software review from the Internet as a source of this extraction process. The extracted software features are compared against the features obtained manually by human and the evaluation results obtained in terms of time, precision, recall, and F-Measure indicate a promising result.